STUDY OF DOS (DENSITY OF STATE) OF HALIDE PEROVSKITES CH3NH3PbI3 USING TROTTER-SUZUKI TIME PROPAGATION METHOD - Perdana, Teguh Iman; Sholihun, Sholihun; Santoso, Imam (JOURNAL ONLINE OF PHYSICS, 2025)
This study investigates the electronic properties of CH₃NH₃PbI₃ using the tight-binding time propagation method (TB-TPM) combined with the Trotter-Suzuki decomposition. The research focuses on computing the density of states (DOS) for various system sizes and time step parameters, employing a real-space approach to model the electronic structures of the material. Considering only the s-orbitals of Pb and I atoms reduces the computational complexity, enabling efficient simulations. The results indicate a metallic behavior, deviating from the expected semiconducting properties reported in prior studies due to the exclusion of critical p-orbital interactions. The study also highlights the effect of timestep size on the accuracy of the correlation functions and DOS, emphasizing the need for smaller timesteps to resolve spectral features effectively.